Chemical Phase Separation of Superconductive and Ferromagnetic Domains in ZnNNi3−xCox - Takahiro Yamazaki; Akira Uehara; Katsuya Kozawa; Yoshihide Kimisima; Masatomo Uehara (Advances in Condensed Matter Physics)
Various ZnNyNi3−xCox compounds with differing Co content, x, were synthesized, and their magnetic properties were investigated. Uniform solid solutions could not be obtained at low Co content (x<0.75); instead micrometer-scaled ferromagnetic ZnNyNi0.6Co2.4 domains formed embedded within a superconductive ZnNNi3 bulk, showing chemical phase separation of superconductive ZnNNi3 and ferromagnetic ZnNyNi0.6Co2.4. At intermediate levels of Co concentration (0.75<x<2), this two-phase separation might persist, and the superconductive behavior was strongly suppressed in this composition region. Only at high Co concentration (x>2) the uniform ferromagnetic solid solution ZnNyNi3−xCox (with most likely y=0.5) formed. The phase separation behavior is intrinsic to the system, reflecting the existence of a miscibility gap in ZnNyNi3−xCox for the samples with x<2, and was shown not to be attributable to incomplete synthesis. In the two-phased samples, high-quality granular contact between the superconductor and ferromagnet has been realized, suggesting that the production of useful devices requiring high-quality contacts between superconductors and ferromagnets may be possible by making use of this two-phase situation.